2015
DOI: 10.1186/s40880-015-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the Epstein-Barr virus genome is strongly associated with a high risk of nasopharyngeal carcinoma

Abstract: BackgroundEpstein-Barr virus (EBV) commonly infects the general population and has been associated with nasopharyngeal carcinoma (NPC), which has a high incidence in certain regions. This study aimed to address how EBV variations contribute to the risk of NPC.MethodsUsing logistic regression analysis and based on the sequence variations at EBV-encoded RPMS1, a multi-stage association study was conducted to identify EBV variations associated with NPC risk. A protein degradation assay was performed to characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Whilst polymorphisms in EBER, EBNA1 (V‐Val), BZLF1 promoter (Zp‐V3), RPMS1 and LMP1 had been proposed to be associated with NPC and other EBV‐associated malignancies, these studies were based on data derived from pre‐selected candidate genes and are prone to detect spurious association due to failure to adjust for the effects of population stratification . To illustrate this point, we analysed the association of these polymorphisms with NPC by chi‐square test in our case–control dataset without considering the population structure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst polymorphisms in EBER, EBNA1 (V‐Val), BZLF1 promoter (Zp‐V3), RPMS1 and LMP1 had been proposed to be associated with NPC and other EBV‐associated malignancies, these studies were based on data derived from pre‐selected candidate genes and are prone to detect spurious association due to failure to adjust for the effects of population stratification . To illustrate this point, we analysed the association of these polymorphisms with NPC by chi‐square test in our case–control dataset without considering the population structure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous case–control studies based on the analyses of candidate EBV genes have reported association between various genetic polymorphisms and NPC . However, these studies are prone to detect spurious association due to the failure to adjust for the confounding effects of population stratification .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next-generation sequencing has revealed large numbers of polymorphisms in the latency-associated genes of EBV (Palser et al, 2015). Notably, a single amino acid polymorphism in EBNA2 confers more efficient immortalization of primary B-lymphocytes (Farrell, 2015), variants in LMP1 are enriched in nasopharyngeal carcinoma (NPC) (Edwards et al, 2004), deletions of EBNA2 are found in Burkitt’s lymphoma (BL) (Kelly et al, 2009), mutations in EBNA3B in Diffuse Large B cell Lymphoma (DLBCL) (White et al, 2012), and mutations in RPMS1 protein correlate with increase NPC risk (Feng et al, 2015). Viruses derived from NPC were also found to have mutations that increased spontaneous lytic reactivity and epithelial cell tropism (Tsai et al, 2013).…”
Section: Genetic Diversity: Strains and Polymorphismsmentioning
confidence: 99%
“…According to statistics of Globocan (2012), the high prevalence of NPC cases was observed the member of the BamHI-A Rightward Transcripts (BARTs) family, RPMS1 expression has been confirmed in all EBV-associated tumors [9][10][11][12][13] . A number of studies have reported attempts to identify the NPC associated EBV genes' variations, including EBV Nuclear Antigens (EBNAs), Latent Membrane Proteins (LMPs) and EBVencoded small nuclear RNAs (EBERs), have been shown to be associated with NPC pathogenesis [14][15][16][17] . However, few studies have investigated the single nucleotide polymorphisms (SNPs) of RPMS1 gene, as the reported, only one SNP site (locus: 155391 G > A, named G155391A) is identified and significantly associated with NPC incidence 16,18 .…”
Section: Introductionmentioning
confidence: 99%